An Analytical Study of Deviations of the Foot and the Way to Put it While Walking Using the Force Sensor - Wissam Shallal Mohamed1, Basem Naji Al-Fatlawi2 , Israalaffta Salem3 , Hayder Naji Habash Alshawi4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The importance of the research lies in knowing the deviations of the foot from the position of the gait and the extent of the relationship of these deviations and the conditions in the pain that occur at the top and bottom of the back, as the method of placing the foot on the ground and areas of strength centring is important and affects the human skeleton, especially the areas of the spine above and below the back, As for the research problem, it was represented by following and informing the researchers. Many people suffer from the pain that arises in the areas of the back. As a specialist in this field, the researchers decided to study and analyze the variables of a force-sensitive device for a sample of students from the College of Basic Education, if this device is through the results that It extracts it can contribute to the knowledge of the many problems that these individuals suffer from at the back level. The research aimed to identify the areas of strength and foot deviations through the force sensor in the research sample, where the researchers used the descriptive method in the survey method as the research community identified the students of the College of Basic Education At the University of Kufa, who are (170) students, and the researchers chose a sample of (20) students who suffer from back pain, and after the presentation and discussion of the results came the most important conclusions The results showed that the research sample rested while walking on the outer part of the foot, and the results showed that the rest of the strength areas of the force were uneven and few.